Nitrogênio hidrolisável em meio alcalino no perfil de solos cultivados com arroz irrigado e sua contribuição para a nutrição da cultura - Drescher, Gerson Laerson (2019)
Rice is an important food source for the world's population and is a substantial crop for Southern Brazil economic development. Nitrogen (N) is one of the most limiting nutrients for rice crop production, and the current N fertilizer recommendation for rice in Southern Brazil is based on soil organic matter (SOM) content at the 0-20 cm layer. However, the recommended N rates are very close for the different SOM classes and there is not always a yield increase by adding fertilizer. In flooded soils, the water input affects the dynamics of SOM decomposition and the N cycle, making it more difficult to predict the N rate based only on SOM content. More accurate N availability indexes, the N evaluation in soil profile and its recovery by rice plants, as well as the effect of N from greater soil depths on rice root morphology can help to improve our understanding on the nutrient dynamics in this production system, while contributing to improve the crop N fertilizer recommendation. This work aims to broaden our understanding of N dynamics in areas cultivated with rice and its relationship with soil properties, as well as identifying the capacity of plants to use N available at greater soil depths. A study was conducted to evaluate the total content and the amount of clay fixed ammonium (CF-NH4) extracted by the Nitrogen Soil Test for Rice (N-STaR) in soils from Arkansas, United States. In soils from southern Brazil, we evaluate the alkaline hydrolyzable N (AH-N) distribution in soil profile and its relationship with soil properties; we investigated the rice N recovery and absorption dynamics from different soil depths; and the effect of N from different soil depths on rice root growth and plant nutrition was also evaluated. The CF-NH4 represents 24.8 and 28.1% of the total N content at the 0-15 and 15-30 cm layers respectively, and the N-STaR estimates that a small proportion (<15%) of this N pool is plant available. These results indicate that CF-NH4 is an important soil N pool and might be a primary N source for rice crop. The AH-N distribution in soil profile is distinct between soils and can have increments in depth. Although granulometric fractions are strongly correlated with AH-N content for some soils, the total N is the major variable dictating AH-N distribution in soil profile. Rice effectively uses available N from depths of up to 45 cm and N recovery is affected by soil physical properties, especially hydraulic conductivity. Higher 15N recovery and N derived from fertilizer occurred when N was applied at the 10, 20 and 30 cm depths, which indicates that the N application in subsurface can increase the nutrient use efficiency by rice crop. The N availability in depth increased the root length, root surface area, and root volume while reducing the root average diameter. The N located at the soil superficial layers is absorbed by the plants in more responsive stages to fertilization, resulting in greater dry mass production. The N located at 30 and 45 cm contributed to plant nutrition at the reproductive stage, increasing the 15N content in the index leaves, the N content in tissue, the chlorophyll content, the photosynthesis rate and the carboxylation efficiency by Rubisco at rice heading. The N available in greater depths than 20 cm contributes to plant nutrition and should be considered in future studies involving the prediction and calibration of N availability indexes for flooded rice.